Contraceptive Method Preference among Conditional Cash Transfer Beneficiaries in Indonesia - Frenty Nurkhalim, Ratna; Susilowati, Indah; Jayanti, Krisnita Dwi (Universitas Ahmad Dahlan, 2020)
Background: Conditional Cash Transfer (CCT) or known as Program Keluarga Harapan (PKH) in Indonesia is a potential program to improve health outcomes, especially reproductive health. This program targeted women from the poor as its beneficiaries. The beneficiaries of this program should visit selected the primary health care to have antenatal care as if they are pregnant. Also, they have to do the growth monitoring regularly if they have children under six. Some studies have found that poor people have a higher risk of unmet need compared to the group with better economies. Could this poor group have a high level of unmet need?. Method:Â A Cross-sectional study of 172 women which all CCT beneficiaries interviewed using a structured questionnaire. We gathered socio-demographic data and the using of contraception from the respondent. The data were analyzed using descriptive method. Results: Contraceptives practice among CCT beneficiaries is relatively high (89.6%) and unmet need for limiting childbirth was 4.1% higher than Indonesia unmet need in 2017.Â Most respondents preferred using pills and injection than any other method and procured it from primary healthcare centre and local/village midwife for free. Conclusion: Pills and injection method were mostly chosen by the respondent. The total unmet need (for limiting) was slightly lower than Indonesia unmet need in 2012. It seems that these CCT beneficiaries donâ€™t meet an obstacle to access contraception. The unmet need for spacing somehow needs further investigation.